The Academic Profession in Canada: Perceptions of Canadian University Faculty about Research and Teaching - Gopaul, Bryan; Jones, Glen A; Weinrib, Julian; Metcalfe, Amy; Fisher, Donald; Gingras, Yves; Rubenson, Kjell (Canadian Journal of Higher Education, 2016)
Previous scholarly attention to the experiences of faculty members has emphasized the contexts of US institutions, with minimal attention to the experiences of faculty members at Canadian universities. This paper presents the findings of the Canadian component of an international survey that was administered in 19 different jurisdictions to understand the perceptions of faculty members about the nature and scope of changes to academic work. As such, the paper explores the perceptions on research and teaching of full-time faculty members affiliated with Canadian universities. Overall, faculty members revealed that Canadian universities have strong, engaging, and vibrant research and teaching environments, yet there are also areas for improvement. Specifically, findings showed that faculty members perceived considerable autonomy with respect to research activities, despite the increasing need to secure external funding for research. Also, faculty expressed substantial commitment to teaching undergraduate students but a lack of clarity about some issues related to graduate teaching. The survey results provide an important baseline for future studies of Canadian universities and the working conditions of the professoriate in a time of rapid institutional and professional change.